Fabrication and characterization of thermochemical hydrogen sensor with laminated structure. (5th January 2017) - Kim, Seil; Song, Yoseb; Lim, Hyo-Ryoung; Kwon, Young-Tae; Hwang, Tae-Yeon; Song, Eunpil; Lee, Songjun; Lee, Young-In; Cho, Hong-Baek; Choa, Yong-Ho
Abstract: In this study, we reported the simple and cost-effective fabrication of thermochemical hydrogen (TCH) sensors composed of chalcogenide thin films and Pt/Al2 O3 powders. Chalcogenide thin films of two types, composed of Bi2 Te3 (monomorphic-type) and Bi2 Te3 Sb2 Te3 (four-leg PN junction-type), were prepared by electrochemical deposition. The Pt/Al2 O3 powder, which acts as a heating catalyst, was synthesized by impregnation of an Al2 O3 powder with an aqueous solution of platinum (IV) chloride pentahydrate. Its heating process was optimized via a hydrogen-sensing evaluation to control the size of the Pt particles. The monomorphic-type TCH sensor showed an output signal of 14.2 μV in response to 10 vol% hydrogen gas, whereas an output signal of 39.6 μV was obtained from a four-leg PN junction–type TCH sensor. Even though the n–p junction-type had the same deposition area as that of the monomorphic-type, the output signal of the n–p junction TCH sensor was greater by a factor of 2.8. In addition, the monomorphic-type TCH sensor had an inferior response time (T90 ) of 31 s and a longer recovery time (D10 ) of 38 s; the four-leg PN junction-type TCH sensor had a lowest response time of 27 s and a fastest recovery time of 9 s (in 3% H2 /air at room temperature). Highlights: Thermochemical hydrogen sensor composed of chalcogenide thin film and Pt/Al2 O3 catalyst was fabricated. Voltage signal of the n–p junction type sensor was higher than monomorphic type sensor. Heat dissipation of n–p junction type sensor was superior to that of monomorphic type one. Response and recovery time of n–p junction type sensor were 27.4 and 9.6 s in 3% H2 /air.